Consumers associate high-quality (fine) wines with complexity, persistence and unpleasant emotional responses - Souza-Coutinho, Maria (2020)
The conventional method for the sensory evaluation of wine is based on visual, olfactory and gustatory perceptions described by a domain-specific language. This is a complex task, requiring extensive training, which is not feasible from a consumer perspective. The objective of this study was to apply a wine tasting sheet, including sensory and emotional responses, to simplify the recognition of fine white wines by consumers. First, a panel of 15 semi-trained judges evaluated eight sensory attributes through Optimized Descriptive Profile (ODP) methodology. Then, a group of 104 consumers evaluated five white wines with di erent sensory characteristics using an improved emotional wine tasting sheet. The emotions and sensations most frequently associated with white wines were obtained through the Check-All-That-Apply (CATA) approach. The eight sensory attributes were significant (p-value < 0.05) in the distinction of wines by the ODP. Likewise, the distinction of the wines also provided significant di erences in all the emotional and sensory attributes (p-value < 0.05). The di erent wine styles could be distinguished by Principal Component Analysis (PCA) using the semi-trained judges or the consumer responses. The highest score in the “global evaluation” was given to two young, fruity wines characterized by high aromatic “initial impression”. The two fine wines, including a 2004 Burgundy Pouilly-Fuissé, were the lowest rated in “initial impression” and “global evaluation”, although they were considered by the consumers among the most complex and persistent. These wines were also most frequently associated with unpleasant emotions by the CATA test. The recognition of these fine wine attributes and their incongruity with emotional responses can be used in a rapid way by professionals to explain the di erent wine styles to consumers